Molecular Detection and Genotyping of Human Papilloma Virus Infections in Iraqi Patients with Esophageal Carcinoma. - Jumaa, Intisar M.; Mohammed Ali, Saad H.; Bakir, Tural Y.; Ardalan, Delaram M. M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Molecular DNA hybridization has confirmed more than 120 different human papilloma virus (HPV) genotypes. A small group of them have high- risk oncogenic potential. Many studies have described an association of such high risk-HPV genotypes with a variety of esophageal benign tumors as well as malignant squamous cell carcinomas. Patients and Methods: A total number of 90 tissue specimens were collected from 50 patients with esophageal squamous cell (SCC), adenocarcinoma (AC) and carcinoma in situ (CIS); 20 patients with squamous acanthosis (SA); and 20 individuals with apparently-healthy esophageal tissues (AHET). The molecular detection methods for HPV detection and genotyping were performed by in situ hybridization using cocktailed- and specific high- risk HPV DNA probes, respectively. Results: The overall percentage of HPV in the total group of esophageal carcinoma was 20%.The percentage of HPV DNA in the subgroup of SCC and AC was 26.7% and 13.3%, respectively,. However, neither HPV DNA was detected in CIS subgroup nor in both control groups (SA and AHET).The overall genotyping results showed that HPV 18 constituted the majority of the detected high-risk oncogenic HPV genotypes, followed by HPV 16 then HPV 31/33. Conclusions: Despite the low prevalence of HPV infection and rarity of invasive esophageal carcinoma in the general Iraqi population, the detection of high percentage of such high oncogenic risk- HPV genotypes in these carcinomas indicating for a relevant importance in esophageal carcinogenesis.